The violence of Jesus and the justice of God : the life, death, resurrection, and Parousia of Jesus as exemplary of non-lethal violent resistance, and the implications for acts of protest by the subaltern - Brown, Alease A. (Stellenbosch : Stellenbosch University, 2019)
Stellenbosch University. Faculty of Theology. Dept. of Systematic Theology and Ecclesiology.